2009
DOI: 10.1007/s11033-009-9879-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MAPK signaling by eNOS gene transfer improves ventricular remodeling after myocardial infarction through reduction of inflammation

Abstract: Endothelial nitric oxide synthase (eNOS) and nitric oxide (NO) may play an important role in attenuating cardiac remodeling and apoptosis after myocardial infarction. However, the anti-inflammation effects of eNOS in infarcted myocardium and the role of MAPK signaling in eNOS/NO mediated cardiac remodeling have not yet been elucidated. Adenovirus carrying Human eNOS gene was delivered locally into heart 4 days prior to induction of myocardial infarction (MI) by left anterior descending coronary artery ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…To elucidate how MIF regulates inflammatory signalling following MI, we performed immunoblotting for p38 and JNK MAPK, both are important in inflammatory signalling post MI [2931]. There was no difference between sham-operated WT and MIFKO groups in levels of phosphorylated p38 or JNK (Figure 4A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate how MIF regulates inflammatory signalling following MI, we performed immunoblotting for p38 and JNK MAPK, both are important in inflammatory signalling post MI [2931]. There was no difference between sham-operated WT and MIFKO groups in levels of phosphorylated p38 or JNK (Figure 4A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many inflammatory response related pathways were also enriched, including complement and coagulation cascades, Fc epsilon RI signaling pathway, hematopoietic cell lineage, leukocyte transendothelial migration, NOD-like receptor signaling pathway, RIG-I-like receptor signaling pathway, and Toll-like receptor signaling pathway. It was suggested that XST modulates inflammatory responses in treating ischemia, which has been found to prevent damages of the inflammatory factors to cardiac cells [3437]. The influencing in complement and coagulation cascades pathway indicated that XST and its constituent compound notoginsenoside R1 are functional in modulating the coagulation process in MI, which is one of the most common clinical risk factors [3235].…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important factors for improving the prognosis after MI is the attenuation of adverse myocardial remodeling and pathological left ventricular hypertrophy. It is well known that several key signaling pathways are involved in the remodeling process, such as the PI3K/Akt (34) and AMPK (35) signaling pathways. Given such complexity in GHSR-1a signaling, we hypothesize that GHSR-1a may play an important regulatory role in cardiac protection.…”
Section: Discussionmentioning
confidence: 99%